Identification of Phytochemical Compounds of Ethyl Acetate Extract of Bulung Anggur (Caulerpa Sp.) By Gc-Ms And Toxicity Test On Artemia Salina Leach Shrimp Larvae - Giwo, Ester; Ti Ha, Nguyen; Wirawan, I Gede Putu; Wijaya, I Nyoman; Suada, I Ketut (International Journal of Biosciences and Biotechnology; Vol 10 No 2 (2023): INTERNATIONAL JOURNAL OF BIOSCIENCES AND BIOTECHNOLOGY, 2023)
Sea grape (Caulerpa sp.) is one of the potential types of seaweed. Sea grape potential as a natural ingredient for making medicine. Balinese people use sea grape for consumption. The content of bioactive compounds in sea grape is suspected to be toxic at certain doses. The purpose of this study was to determine the compound content of ethyl acetate extract of sea grape (Caulerpa sp.) and the toxicity on Artemia salina Leach. The identification of the bioactive compounds was carried out by Gas Chromatography-Mass Spectrophotometry and the toxicity test of extracts was carried out using the Brine Shrimp Lethality Test (BSLT) method. The results showed that the ethyl acetate extract of sea grape (Caulerpa sp.) contained 27 chemical compounds, 7 of which had a quality value > 70%, namely Propanoic acid, ethyl ester; n-Propyl acetate; sec-Butyl acetate; Toluene; Acetic acid, butyl ester; Bicyclo [4.2.0] octa-1, 3, 5-triene; and Styrene. The results of the toxicity test of Artemia salina Leach are toxic which had an LC50 value of 44,070 ppm so that they can be used as a larvicide